Seborrheic dermatitis: comparative effectiveness of standard and intermittent external therapy - Evgeny A. Vasiliev-Stupalsky (Vestnik Dermatologii i Venerologii, 2020)
Background. The chronic and recurrent nature of seborrheic dermatitis, its wide prevalence and multifactorial etiopathogenesis require a comparison of the effectiveness of different treatment strategies.